2020
DOI: 10.2147/copd.s230188
|View full text |Cite
|
Sign up to set email alerts
|

<p>Glucocorticoid Receptor α Mediates Roflumilast’s Ability to Restore Dexamethasone Sensitivity in COPD</p>

Abstract: Background: Glucocorticoids are commonly prescribed to treat inflammation of the respiratory system; however, they are mostly ineffective for controlling chronic obstructive pulmonary disease (COPD)-associated inflammation. This study aimed to elucidate the molecular mechanisms responsible for such glucocorticoid inefficacy in COPD, which may be instrumental to providing better patient outcomes. Roflumilast is a selective phosphodiesterase-4 (PDE4) inhibitor with antiinflammatory properties in severe COPD pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
(58 reference statements)
0
12
0
Order By: Relevance
“…The mechanism of the interaction between corticosteroids and cAMP-elevating agonists remains uncertain (Taylor and Hancox, 2000). In neurons, synergism between forskolin and dexamethasone has been ascribed to cAMP upregulation of glucocorticoid receptor (GR) expression (Scarceriaux et al, 1995) while roflumilast enhances the expression of GRα in COPD pHBE cells after 6 h treatment (Reddy et al, 2020). However, we did not observe an effect of ensifentrine on GR mRNA expression, perhaps due to our analysis of GR expression occurring later (24 h) than in previous studies.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The mechanism of the interaction between corticosteroids and cAMP-elevating agonists remains uncertain (Taylor and Hancox, 2000). In neurons, synergism between forskolin and dexamethasone has been ascribed to cAMP upregulation of glucocorticoid receptor (GR) expression (Scarceriaux et al, 1995) while roflumilast enhances the expression of GRα in COPD pHBE cells after 6 h treatment (Reddy et al, 2020). However, we did not observe an effect of ensifentrine on GR mRNA expression, perhaps due to our analysis of GR expression occurring later (24 h) than in previous studies.…”
Section: Discussionmentioning
confidence: 55%
“…The effects were mirrored in welldifferentiated pHBE cells, indicating that using drugs in combination has more potent anti-inflammatory effects than either drug alone. PDE4 inhibition has previously been shown to enhance corticosteroid-induced activation of the GRE in BEAS-2B and pHBE cells and potentiate dexamethasone-induced downregulation of IL-8 and TNFα in pHBE cells from COPD patients (Moodley et al, 2013;BinMahfouz et al, 2015;Reddy et al, 2020). Furthermore, in human airway epithelia, TNF-α-stimulated GM-CSF production is significantly reduced in cells treated with both the glucocorticoid budesonide and the cAMP-elevating formoterol (Korn et al, 2001) with these effects of budesonide and formoterol further enhanced when MRP4-dependent cAMP efflux is also blocked (Huff et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, roflumilast was reported to reverse the corticosteroid-associated insensitivity towards neutrophils in COPD patients (Milara et al, 2015b). As well, other study revealed the great value of roflumilast in restoring the glucocorticoid sensitivity in glucocorticoid-resistant patients through blocking the downregulation of glucocorticoid receptor alpha (GRα), which was known to be responsible for glucocorticoid resistance (Reddy et al, 2020).…”
Section: Roflumilast and Lung Inflammationmentioning
confidence: 94%
“…At the same time, roflumilast was reported to reverse the corticosteroid-associated insensitivity towards neutrophils in COPD patients ( Milara et al, 2015b ). As well, other study revealed the great value of roflumilast in restoring the glucocorticoid sensitivity in glucocorticoid-resistant patients through blocking the downregulation of glucocorticoid receptor (GRα) alpha, which was known to be responsible for glucocorticoid resistance ( Reddy et al, 2020 ).…”
Section: Pharmacotherapeutic Effects Of Roflumilastmentioning
confidence: 99%